Mental health in the United States: An appraisal of advances and problems - Iscoe, Ira (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
As with all movements, the present situation with regard to the improved condition in the delivery of mental health services to the United States did not come about overnight. Without taking too much time to go too far back into historical antecedents, it should be mentioned that a Task Force was created by the United States Congress in 1955, and this Task Force on Mental Health and Mental Illness worked for five years, produced some ten reports, and climaxed its work by the publication of a book entitled Action Against Mental Illness.